2020
DOI: 10.1186/s12884-020-03443-4
|View full text |Cite
|
Sign up to set email alerts
|

Do you pay to go private?: a single centre comparison of induction of labour and caesarean section rates in private versus public patients

Abstract: Background The aim of this study was to compare rates of induction and subsequent caesarean delivery among nulliparous women with private versus publicly funded health care at a single institution. This is a retrospective cohort study using the electronic booking and delivery records of nulliparous women with singleton pregnancies who delivered between 2010 and 2015 in an Irish Tertiary Maternity Hospital (approx. 9000 deliveries per annum). Methods Data were extracted from the National Maternity Hospital (NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…However, there is some work showing that, when labour is induced in nulliparous women in Australia, the CS rate increases from 12% to 22% [ 20 ] or, in Ireland, from 19% to 29% [ 21 ]. Another Irish study comparing IOL and CS rates in ‘private versus public patients’ showed that the CS rate for all women following spontaneous onset of labour was 9.22%, compared with a CS rate of 31.25% following IOL [ 22 ], which lends credence to our participants’ views. This may be a uniquely Irish problem, perhaps due to different methods used for IOL, or differing gestational ages used as a criterion for induction, as IOL with an unripe cervix is more likely to lead to a ‘failed’ induction, a principal cause of CS [ 23 ].…”
Section: Discussionsupporting
confidence: 74%
“…However, there is some work showing that, when labour is induced in nulliparous women in Australia, the CS rate increases from 12% to 22% [ 20 ] or, in Ireland, from 19% to 29% [ 21 ]. Another Irish study comparing IOL and CS rates in ‘private versus public patients’ showed that the CS rate for all women following spontaneous onset of labour was 9.22%, compared with a CS rate of 31.25% following IOL [ 22 ], which lends credence to our participants’ views. This may be a uniquely Irish problem, perhaps due to different methods used for IOL, or differing gestational ages used as a criterion for induction, as IOL with an unripe cervix is more likely to lead to a ‘failed’ induction, a principal cause of CS [ 23 ].…”
Section: Discussionsupporting
confidence: 74%